[PP.32.06] CARDIOVASCULAR RISK MANAGEMENT IN THE FRENCH WEST INDIES: BETTER COORDINATION NEEDED. (September 2016) - Carrère, P.; Hérin, M.; Hélène-Pelage, J.; Inamo, J.; Atallah, A.; Lang, T.
Abstract : Objective: Since 2004, the implementation of coordinated care pathways in France has made the referring physician, usually a general practitioner, responsible for coordinating care of outpatients. Nevertheless, considerable social inequalities in health remain. This is particularly true in the French overseas departments, which present highly unequal health outcomes. Our objectives: were to evaluate secondary access to medical care and social services in a population at risk for cardiovascular disease in the French West Indies. Design and method: A multicenter cross-sectional study was conducted in Guadeloupe between July and December 2014, including all patients aged 18–74 receiving a systematic periodic health examination funded by social security (2255 subjects). Diabetes was defined by antidiabetic treatment or fasting plasma glucose >= 7 mmol/L and glycated hemoglobin >= 6.5%, and controlled diabetes by glycated hemoglobin < 7%. Hypertension was defined by antihypertensive treatment or mean of 3 measurements of blood pressure >= 140/90mmHg. Access to a referring physician, cardiologist or endocrinologist and social workers were evaluated by questionnaire. Food insecurity was defined as self-reported difficulty in meeting basic needs. Multilevel logistic regression was used for analysis. Results: Among participants, 35.1% had hypertension and/or diabetes. That proportion fell to 25.3% for subjects with at least a middle school diploma and rose to 48.8% for those with less education (center-, sex- and age-adjusted OR = 1.72; p < 0.001). Among the 76.7% of subjects with hypertension and/or diabetes who had seen their referring physician during the past year, 62.9% had uncontrolled hypertension and/or diabetes. Among this last group, 58% had consulted neither a cardiologist nor an endocrinologist. That proportion rose to 66.7% for subjects with income limited to welfare and fell to 42.4% for those with higher income (adjusted OR = 2.7;p = 0.004). Among the 56.4% of subjects with uncontrolled hypertension and/or diabetes who were also food insecure, nine in ten had never met with a social worker, regardless the number of consultations they had with their referring physician in the preceding year. Conclusions: In this at-risk French Caribbean population, secondary access to medical care and social services was deficient. Coordination of care must be improved.